PENGARUH PELAYANAN TERHADAP TINGKAT KEPUASAN NASABAH PADA PT BANK CENTRAL ASIA, Tbk KCP ROXY MAS - Supardi (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2022)
PT Bank Central Asia, Tbk Roxy Mas Branch continues to raise funds from the public. To achieve this, the right strategy is needed through optimal service by improving the quality of products and services in accordance with the wishes and needs of customers. By knowing the level of customer satisfaction, it can be seen how far the services that have been provided by employees / staff. Satisfied customers are customers who get value from suppliers, manufacturers or service provider. Value can be a service, product or system or something that is emotional. If the customer states that value is quality product, then satisfaction occurs when the customers gets a quality products. If the value gets comfort, then satisfaction is obtained if the service provided is really comfortable and satisfying. If the value of customer, is a low price the customer will be satisfied with the producer who provides the most competitive price.